JUSTIFICATION OF THE CHOICE OF OPTIMAL PROBIOTIC THERAPY OF ACUTE INTESTINAL INFECTIONS IN CHILDREN WITH FUNCTIONAL AND CHRONIC DISORDERS OF GASTROINTESTINAL TRACT - E. R. Meskina; N. M. Bochkareva (LLC "Diagnostics and Vaccines", 2015)
Studied the comparative efficacy of probiotics with different composition of strains in the complex treatment of acute intestinal infection in 89 children with functional disorders and chronic gastrointestinal tract. Conducted a dynamic study of the intestinal microflora bacteriological method and gas-liquid chromatography with the definition of short-chain fatty acid content of the level of carbohydrates in the feces and stool data. Set different dates for stopping diarrhea and features state of the intestinal ecosystem indicators after treatment in patients receiving comprehensive probiotic containing bifidobacteria and enterococcus, or probiotic containing lactobacillus.